Do We Really Understand Problems of Rubber Farmers with Small Areas in the Recent Extension Area in Upper Northeast Thailand? - Borisutdhi, Yos; Wansri, Nipapan; Kaewmanee, Sommai; Mikhama, Kanlaya; Simaraks, Suchint (Kasetsart Journal of Social Sciences, 2014)
Northeast Thailand is an important area of Para rubber production in upstream catchments. The initial study on the general situation of rubber production by farmers with small holdings in the new plantation target area, found that their production practices were not in accordance with those recommended by extension workers and academic reports such as the processing of latex into a rubber cup lump instead of a rubber sheet, tapping rubber latex before the rubber trees have reached an appropriate size or before age seven years, tapping the latex during leaf-fall, too close spacing between trees, and planting rubber trees in shallow topsoil or on inappropriate land. However, are these problems really farmers’ problems and why? Further study tried to find out the answers to these questions. So Phisai district, Bueng Kan province was purposively selected for this study. A semi-structured interview was employed for qualitative data collection from key informants, leading farmers, farm households, farmer organization committee, cup lump bidding purchasers, and fresh rubber purchasers. This study was carried out during November 2010 and June 2011. The results were contradictory to the above-identified problems. The real, prioritized problems of the farmers studied could be classified into farmer organization and farmer household levels. At the farmer organization level, the main issues were: limited market choice and unstable price of rubber, late purchase and payment by the bidder, low quality or standard of rubber cup lump, insufficient revolving fund of the farmer organization, and the reduction of the rubber cup lump selling operations of the farmer organizations by the fresh rubber cup lump purchasers. At the household level, the problems were: limited market choice and unstable price of rubber, diseases and insect pests, theft of rubber cup lump in rubber plantation, limited skilled labor available, and health-related problems due to the change in livelihood patterns resulting from rubber production. Therefore, recommendations for problem solving should not only focus on the technical but also on the social aspects of the rubber farmers.